Rift Valley fever: Prevention and control - International Livestock Research Institute (International Livestock Research Institute, 2018)
Rift Valley fever is a viral disease that affects sheep, goats and camels and cattle resulting in abortion and deaths in young animals. It also affects humans. This film explains the the signs of Rift Valley fever in animals and ways of preventing and controlling the disease.